Podrobnosti . Podrobnosti . Details . Подробности - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the prospects for creating a new democratic party in Russia; the influence of the Bosnian crisis on Russia. Featured in the program: Gaidar, Egor Timurovich (Deputy of the State Duma) Contributors: Svanidze, Nikolai (Anchor); Dorenko, Sergei (Anchor) Обсуждение перспектив создания новой партии демократов в России; влияние боснийского кризиса на Россию. В программе участвуют: Гайдар, Егор Тимурович (Депутат Государственной Думы) Создатели: Сванидзе, Николай (Ведущий/Ведущая); Доренко, Сергей (Ведущий/Ведущая)